ENVIRONMENTAL SUSTAINABILITY IN AGRICULTURE: DIFFERENT WAYS OF QUANTIFICATION - Czyżewski, Bazyli; Matuszczak, Anna; Muntean, Andrea (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The main goal of the article is to compare three approaches to measuring environmental sustainability in agriculture: (1) environmental burden index, (2) sustainable value of eco-efficient production and (3) sustainable value of eco-effective farm, applied by the authors to the sample of 125 EUFADN regions in 2015. The study indicate a fundamental problem: the notion of environmental sustainability in agriculture differs depending on the criterion we apply. The authors recognized a principle trade-off in CAP which consist of compensating strain on the natural environment with production or with public goods provision. The choice between these two effects is crucial to draw a consistent development path for the Common Agricultural Policy.